Neuordnung der Finanzierung des ÖPNV notwendig. - Berg, Claus C.; Sterzenbach, Tim (Deutscher Verkehrs-Verl., 2007)
Die herausragende Bedeutung des ÖPNV ist von den politischen Entscheidungsträgern auf allen gebietskörperschaftlichen Ebenen anerkannt und in zahlreichen verkehrspolitischen Programmen und Stellungnahmen betont worden. Die allgemeinen politischen Zielsetzungen für den ÖPNV sind dabei über sämtliche gebietskörperschaftliche Ebenen hinweg ähnlich. Jedoch zeichnet sich auch im ÖPNV seit einiger Zeit ein zunehmender Einfluss der europäischen Ebene auf die nationale Nahverkehrspolitik ab. difu

The present system of financing for the ÖPNV is apparently not effective enough with regard to its tariff set-up or quality effect. Furthermore, a lack of transparency and process efficiency - coupled with a noteworthy strategy-related vulnerability - tends to adversely affect the system's efficiency. Because of the deficiencies of the existing ÖPNV financing system, a fundamental revision would seem appropriate. An analysis of competitive and economic factors points to the fact that market conditions are deemed to offer - also within the ÖPNV system - the optimum way for the allocation of public transport services. The obvious failure in competition renders the principle of free market access to the ÖPNV network (traffic and infrastructure) unworkable. difu
Keywords: Öffentlicher Verkehr; ÖPNV; Finanzierung; Verkehrspolitik; Verkehrsunternehmen; Nahverkehr; Finanzierungsmodell; Regionalisierung; Wettbewerb; Verkehrsinfrastruktur; Verkehrsleistung